PENGARUH WAKTU PENYIMPANAN BENIH DAN KONSENTRASI LARUTAN ASAM SULFAT TERHADAP VIABILITAS DAN VIGOR BENIH JARAK (Jatropha curcas Linn) DI PERSEMAIAN - Kovertina Rakhmi Indriana (Paspalum: Jurnal Ilmiah Pertanian, 2016)
The purpose of the research study the viability and vigor of plants in the nursery and look for the optimum concentration of H2SO4 solution at each storage duration that gives the distance of the highest seed viability in the nursery. Experiments conductedin the seed laboratory and in the nursery Faculty of Agriculture Winaya Mukti University Tanjungsari using randomized block design (RBD) factorial, first factor the time and concentration of sulfuric acid solution: Soaking 6 minutes in H2SO4 0.25%, 0.50%, 0.75% and 1.0%. Factor II is a seed storage duration: without being stored, 1, 2, 3 months. Analysis of the data using linear quadratic regression method. The experimental results show that the interaction between seed storage time and concentration of sulfuric acid solution on seed germination, growth speed of seeds, and seed vigor. Without storage time and concentration of sulfuric acid solution 0.75% gives the best effect compared to other treatments. At the time of storage, followed without the optimum sulfuric acid concentration as much as 0.783% gives the percentage of seed germination was 93.521%.